Exploration of the best reference material on anelastic measurement by cyclic loading under high pressure. Issue 1 (2nd January 2022) - Liu, Chao; Yoshino, Takashi; Yamazaki, Daisuke; Tsujino, Noriyoshi; Gomi, Hitoshi; Sakurai, Moe; Zhang, Youyue; Wang, Ran; Guan, Longli; Lau, Kayan; Tange, Yoshinori; Higo, Yuji
ABSTRACT: Anelastic measurement by cyclic loading under high pressure has been developed by means of in situ X-ray observation at a synchrotron facility. In this method, the reference material is a key factor to precisely determine attenuation and moduli of unknown materials. We compared the performance of three types of reference materials (dense polycrystalline alumina, alumina single-crystal parallel to c -axis, and flexible graphite) under the pressure of 3 GPa and the temperature range between 1173 and 1373 K. The phase lags of strain between reference materials and samples show that the flexible graphite is less attenuated than dense polycrystalline alumina and alumina single crystal in various periods. The strain ratios show that the flexible graphite is much softer and can produce the measurable strain in the limited displacement. The flexible graphite, as reference material, is more excellent to detect the relatively lower energy dispersion of mantle minerals at high pressure.